2020
DOI: 10.1093/mnras/staa3852
|View full text |Cite
|
Sign up to set email alerts
|

The physical and the geometrical properties of simulated cold H i structures

Abstract: The objective of this paper is to help shedding some light on the nature and the properties of the cold structures formed via thermal instability in the magnetized atomic interstellar medium. To this end, we searched for clumps formed in forced (magneto)hydrodynamic simulations with an initial magnetic field ranging from 0 to 8.3 μG. We statistically analysed, through the use of Kernel density estimations, the physical and the morphological properties of a sample containing ∼1500 clumps, as well as the relativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…The density at which this correlation becomes significant (n H < ∼ 30 cm −3 ) depends on the initial conditions but is not sensitive to the presence of self-gravity. Figure 2 of Gazol & Villagran (2021) shows that the resulting clumps have a wide range of magnetic field intensities, which is similar to the large scatter that we observe here. The magnetic field in the simulations, albeit weak, qualitatively affects the morphology by producing filamentary structures.…”
Section: Filaments At the Rim Of The The Local Bubblesupporting
confidence: 84%
See 1 more Smart Citation
“…The density at which this correlation becomes significant (n H < ∼ 30 cm −3 ) depends on the initial conditions but is not sensitive to the presence of self-gravity. Figure 2 of Gazol & Villagran (2021) shows that the resulting clumps have a wide range of magnetic field intensities, which is similar to the large scatter that we observe here. The magnetic field in the simulations, albeit weak, qualitatively affects the morphology by producing filamentary structures.…”
Section: Filaments At the Rim Of The The Local Bubblesupporting
confidence: 84%
“…Studying the nature and the properties of the cold structures formed via thermal instability in the magnetized atomic ISM, Gazol & Villagran (2018) and Gazol & Villagran (2021) searched for clumps formed in forced MHD simulations with an initial magnetic field ranging from 0 to 8.3 µG. These authors find that a positive correlation between B and n H develops for all initial magnetic field intensities.…”
Section: Filaments At the Rim Of The The Local Bubblementioning
confidence: 99%
“…The morphologies of CNM structures contain imprints of a complex interplay between thermal instability, shock compression, turbulence, and magnetic fields at different scales. The connections between CNM morphology and the conditions of its multiscale turbulent ISM environment have been studied with numerical simulations (Hennebelle et al 2007;Saury et al 2014;Inoue & Inutsuka 2016;Gazol & Villagran 2021;Fielding et al 2022). The ST, with its set of interpretable coefficients at different scales and orientations, can enable convenient quantitative comparisons between observations and simulations.…”
Section: Discussionmentioning
confidence: 99%
“…From simulations, it has been suggested that filamentary H structures can be formed by turbulence, shocks, or thermal instabilities, with the role of the magnetic field still under debate (e.g., Hennebelle 2013;Federrath 2016b;Inoue & Inutsuka 2016;Villagran & Gazol 2018;Gazol & Villagran 2021). In fact, various numerical studies have led to results ranging from no preferred orientation of the H filaments with respect to the magnetic field (Federrath 2016b), to the filaments preferentially oriented parallel (Inoue & Inutsuka 2016;Villagran & Gazol 2018) or perpendicular (Gazol & Villagran 2021) to the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…From simulations, it has been suggested that filamentary H structures can be formed by turbulence, shocks, or thermal instabilities, with the role of the magnetic field still under debate (e.g., Hennebelle 2013;Federrath 2016b;Inoue & Inutsuka 2016;Villagran & Gazol 2018;Gazol & Villagran 2021). In fact, various numerical studies have led to results ranging from no preferred orientation of the H filaments with respect to the magnetic field (Federrath 2016b), to the filaments preferentially oriented parallel (Inoue & Inutsuka 2016;Villagran & Gazol 2018) or perpendicular (Gazol & Villagran 2021) to the magnetic field. Extending the observational study of the relative orientation between magnetic fields and H filamentary structures to nearby galaxies is therefore crucial, as the simpler external perspective will allow us to verify, despite the very different spatial scales probed, if the magnetically aligned H filaments are a general trend across a vast galactic volume.…”
Section: Introductionmentioning
confidence: 99%